Making a Case for the Usefulness of the Traditional Curriculum in Indian Settings - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava (Journal of Integrated Health Sciences)
In the field of delivery of medical education in India, the adoption of Competency Based Medical Education (CBME) has been regarded as one of the most important landmarks in the timeline of the profession. Even though, we have shifted altogether to CBME, it is not right to consider that there were no positive attributes which were linked with traditional curriculum. We have to accept that CBME is a resource-intensive program in comparison to the traditional curriculum and thus in order to ensure its successful implementation, we have to adopt the better components of traditional curriculum and improve the assessment process as a whole. In conclusion, the traditional curriculum in medical education has played a very crucial role in the making of a wide range of specialists and doctors for prolonged durations. Although, some important attributes of a medical professional were not given much attention, we have to accept the fact that it was very much required for the successful launch and implementation of Competency-Based Medical Education in the nation.